CFD analysis of effect of Mach number, area ratio and nozzle pressure ratio on velocity for suddenly expanded flows - Pathan, Khizer Ahmed; Khan, Sher Afghan; Dabeer, P S (IEE, 2017)
This paper presents the Computational Fluid Dynamic (CFD) analysis to study the effect of Mach numbers on velocity distribution at different area ratio and nozzle pressure ratio in the flow field from convergent-divergent nozzles to a suddenly expanded circular duct of larger cross-sectional area. The study is focusing on velocity distribution along axial length. The analysis is done for Mach numbers 1.4 and 1.8 by varying the area ratios and nozzle pressure ratios. The area ratios for the analysis are 1, 2, 4, 6, 8, 10 and 12. The values of nozzle pressure ratios considered for analysis are 2, 4, 6, 8, 10 and 12. The results are plotted with the help of graphs. By observing all the results it can be concluded that the flow field in the enlarged duct is strongly influenced by Mach numbers, area ratios and Nozzle pressure ratios.